Communication and Meaning An Essay in Applied Modal Logic - Jones, A.J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 1983)
This essay contains material which will hopefully be of interest not only to philosophers, but also to those social scientists whose research concerns the analysis of communication, verbal or non-verbal. Although most of the topics taken up here are central to issues in the philosophy of language, they are, in my opinion, indistinguishable from topics in descriptive social psychology. The essay aims to provide a conceptual framework within which various key aspects of communication can be described, and it presents a formal language, using techniques from modern modal logic, in which such descriptions can themselves be formulated. It is my hope that this framework, or parts of it, might also turn out to be of value in future empirical work. There are, therefore, essentially two sides to this essay: the development of a framework of concepts, and the construction of a formal language rich enough to express the elements of which that framework is composed. The first of these two takes its point of departure in the statement quoted from Lewis (1972) on the page preceding this introduction. The distinction drawn there by Lewis is accepted as a working hypothesis, and in one sense this essay may be seen as an attempt to explore some of the consequences of that hypothesis.
I: Signs and Signalling -- I.1. Lewis on Signalling Systems -- I.2. Signs and Meaning -- I.3. Sign Systems and the Possibility of Deceit -- I.4. Generalization of Rules of Information -- I.5. ISS$1 (Bs and Lewis Indicative Signalling Systems -- I.6. Conventions of Truthfulness and Trust v. Rules of Information -- II: A Formal Language -- II.1. LC: its Syntax and the General Form of its Semantics -- II.2. Action Modalities -- II.3. Normative Modalities -- II.4. The Belief Modality -- II.5. Mutual Belief -- II.6. The Modality Va -- II.7. Deontic Modalities -- II.8. Knowledge that p -- II.9. On the Alleged Circularity of Possible-World Semantics -- III: Some Features of Communication Situations -- III.1. Truthfulness and Trust -- III.2. Moore$1 (Bs Paradox of Saying and Disbelieving -- III.3. Informing and Asserting -- III.4. Trust of Type No-Deceit, Communicators$1 (BIntentions and (3z(BSaying One Thing and Meaning Another(3y (B-- III.5. Non-Deceiving Performances and the Implementation of Rules of Information -- IV: Non-Indicatives -- IV.1. Non-Indicatives and Truth Conditions -- IV.2. Performatives -- IV.3. Sketch for a Logic of Imperative Inference -- IV.4. Other Types of Non-Indicatives -- IV.5. Non-Indicative Usage of Indicatives -- V: Intention-Dependent Evidence -- V.1. Bennett$1 (Bs Defence of the Gricean Theory -- V.2. The Modality Shall and the Analysis of Signalling -- VI: The Double Bind -- VI.1. General Features of a Double-Bind Situation -- VI.2. The Illustration from Clinical Data $1 (Ba Formal Description -- VI.3. Bateson$1 (Bs Theory of Communication -- VI.4. The Double Bind and Levels of Communication -- Concluding Remarks -- Index of Names -- Index of Subjects.s
Keywords: Language and languages$1 (BPhilosophy.s; Logic; Philosophy of Language; Logic